Lipophilic antioxidants in wheat (Triticum spp.): A target for breeding new varieties for future functional cereal products. (January 2016) - Ziegler, Jochen U.; Schweiggert, Ralf M.; Würschum, Tobias; Longin, C. Friedrich H.; Carle, Reinhold
Highlights: Lipophilic antioxidants were quantitated in 75 varieties of five wheat species. Vitamin E, lutein, alkylresorcinol, and steryl ferulate levels significantly varied. Whole grain flours of all varieties of the species einkorn showed highest contents. Concentration of lipophilic antioxidants was mainly determined by genetic factors. Abstract: Lutein, tocochromanols (vitamin E), alkylresorcinols, and steryl ferulates were quantitated in whole grain flours of 15 varieties each of bread wheat, spelt, durum, emmer, and einkorn grown in four different environments. In a comprehensive screening, these bioactive compounds were selected as target traits to identify high yielding varieties regarding their lipophilic antioxidant contents, using standardised total concentrations (z-scores). Einkorn was found to be the species containing maximum overall levels of lipophilic antioxidants, and all 15 einkorn varieties ranked among the top 20 high antioxidant yielding varieties. Among the five different wheat species, high crop yields and protein contents did not mutually exclude high levels of lipophilic micronutrients. The high heritability of lipophilic antioxidants indicated that their concentrations are mainly determined by genetic factors. Thus, in future breeding programmes, wheat varieties being even richer in lipophilic antioxidants may be obtained, allowing the production of functional cereal products with improved nutritional value.